High salt intake combined with hypertension elevated the risk of primary liver cancer: a prospective cohort study - Liu, Tong; Zhang, Qingsong; Xiao, Xiaoli; Wang, Yiming; Ma, Xiangming; Song, Mengmeng; Zhang, Qi; Cao, Liying; Shi, Hanping (Frontiers in Oncology, 2022)
Abstract Background: Hypertension and high-salt intake may act synergistically to increase the risk of primary liver cancer (PLC). We prospectively examined the joint effect of hypertension and salt intake on the risk of PLC incidence. Methods: A total of 92,978 participants were included in the final analyses. The study population was divided into 4 groups according to the presence or absence of hypertension and salt intake. Cox proportional hazards regression models were used to evaluate the association of hypertension and/or high-salt intake with the risk of incident cancers. Results: During a median follow-up of 12.69 years, a total of 418 incident cancer cases were identified. Hypertension was a risk factor for PLC in women but not in men. And high salt intake was associated with an elevated risk of PLC in men but not in women. A significant interaction between salt intake and hypertension was found for the risk of PLC (P for interaction=0.045). Compared with Group 1 (hypertension-, high salt intake-), participants in Group 2 (hypertension-, high salt intake+) and Group 4 (hypertension+, high salt intake+) were associated with an elevated risk of PLC with the corresponding multivariate HRs (95%CIs) of 1.73(0.96,3.10) and 1.96(1.09,3.53), respectively. No significant mediation effect was found for the association between hypertension, salt-intake and PLC risk. Conclusions The combination of high salt intake and hypertension could significantly increase the risk of PLC. It may be reasonable to recommend a low-salt intake to prevent and control the prevalence of PLC and hypertension.